Distribution and risk factors for stress fractures in competitive figure skaters and association with acute fractures - Nayler, T. A.; Nayler, S. (The Physician and Sportsmedicine, 2023)
Introduction Figure skating combines esthetic components with high impact, technically demanding elements requiring high volume repetitive training. The evidence base for the sport is limited, particularly regarding stress fracture injuries. This study aims to describe the prevalence and anatomical distribution of stress fracture injuries and assess for risk factors, as well as associations with acute fractures.